Acid Hydrolysis of Chitosan to Oligomers Using Hydrochloric Acid - Aljbour, Nawzat D.; Beg, M. D. H.; Jolius, Gimbun (Wiley, 2019)
The natural polymer chitosan is widely used for medical and drug delivery applications. Low molecular weight chitosan (LMWC) has superior properties compared to high molecular weight chitosan (HMWC), which open new applications of LMWC, especially in the cosmetics, food, and pharmaceutical industries. LMWC is often produced from HMWC by acid, enzymatic, or oxidative hydrolysis. Industrially, hydrolysis with dilute HCl is preferred, since it is simple, practical, and gives a high yield. In this study 2M HCl was used to prepare LMWC. A high average depolymerization yield of 87% was obtained. The LMWCs were characterized by FTIR spectroscopy, and the molecular weight and degree of deacetylation were determined. The prepared LMWCs are fully deacetylated, and their production by this method is reproducible.